The Influence of Work Motivation and Non-Physical Work Environment on Employee Performance in the Body and Paint Section of PT Auto 2000 Astra International Tbk Bandar Lampung - Novaldi, Rizki; Puji, Kemala (Universitas Pamulang, 2024)
This study aims to test and analyze the influence of Work Motivation and Non-Physical Work Environment on Employee Performance in the Body and Paint section of PT. Auto 2000 Astra International Tbk Bandar Lampung. The population in this study is 32 employees with saturated sampling, namely all members of the population. The research is a quantitative research with a descriptive analysis method. The data analysis used includes: validity test, reliability test, descriptive statistical analysis test, and multiple linear regression test. As well as hypothesis testing in the form of T Test (Partial Test), F Test (Simultaneous Test) and R2 (Determination Coefficient Test). The results of this study show that the Work Motivation variable partially has a positive and significant effect on Employee Performance. Non-Physical Work Environment variables partially have a positive and significant effect on Employee Performance. Simultaneously, the variables of work motivation and non-physical work environment together have a positive and significant effect on Employee Performance in the Body and Paint section of PT. Auto 2000 Astra International Tbk Bandar Lampung with a contribution of 62.7% of the influence that can be explained by the independent variable (work motivation and non-physical work environment) on the bound variable (employee performance), while the remaining 37.3% is explained by other variables that were not tested in this study.